Inside Bob Dylan's Jesus years : busy being born... again! - Gilbert, Joel; Highway 61 Entertainment; Soundview Media Partners ([Irwindale, Calif.] : Highway 61 Entertainment, 2008)
At first called "Dylan's God-Awful Gospel" by his most loyal fans, Bob Dylan's Jesus Years is today regarded as among the best of his career. How did a Jewish folk singer from the mid-west come to Jesus? Finally, here is an insider's view of Bob Dylan's "Born Again" transformation, and its effects on his life and music. In late 1978 Bob Dylan fell into the arms of the Lord through the Vineyard Christian Fellowship Church. In his first-ever interview, Dylan's bible class teacher details Dylan's embrace of Jesus Christ and Christianity. Dylan then made three Gospel albums, winning a Grammy for Gotta Serve Somebody. However, Dylan's radical new direction alienated fans and enraged critics as he preached apocalyptic messages for the Book of Revelation. Director Joel Gilbert weaves the intimate story Inside Bob Dylan's Jesus years through revealing interviews.
Originally produced as a motion picture in 2008.
Interviewer: Joel Gilbert.
Cinematographer, ; editors, Paul Belanger, Joel Gilbert ; music, Highway 61 Revisited with Scarlet Rivera & Burce Langhorne.
In English with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Dylan, Bob, -- 1941- -- Religion; Rock musicians -- United States; Popular music -- 1971-1980 -- History and criticism; Gospel music -- History and criticism; Biographical films; Nonfiction films; Documentary films; Internet videos; Streaming video